(untitled) (Palíndromo, 2022)
Educational technologies are included in the curriculum of many Higher Education Institutions, in order to prepare students with a basic knowledge of the subject. This work has as main objective to observe the insertion of technologies in the curriculum of the degree course in Visual Arts at the Federal University of Maranhão – UFMA, analyzing, in a comparative way, the Pedagogical Projects of 2010 and 2017. The results obtained indicate that the technologies are addressed in some disciplines such as Art and new technologies, among others that aim to meet the restructuring of the Visual Arts course, and meet the demand of an audience that is interactive and connected. For this study, we opted for documentary research, case study and bibliography, basing the discussion on the conceptions of authors such as Pimentel (2011), Cernev and Guerra (2017), Frizon (2015), Moran (2013), among others. Thus, it is expected that the concerns about the initial training of Art teachers raised throughout the work contribute to the reflection on the need to combine theory and teaching practice through the creation and expansion of new pedagogical practices that enhance the use of digital technologies in the classroom.